Assessment of an Integrated Nutrition Communication Approach to Educate the School Going Adolescent Girls Living In Urban Slums of Hyderabad, Telangana State, India - Rao, D. Raghunatha; Vijayapushpam, T.; Rao, N. Amulya; Dube, Anilkumar; Venkaiah, K. (Asian Journal of Education and Training, 2016)
Purpose: Consumption of right diet during the adolescent phase is a critical issue among the adolescent population as their eating behavior is significantly influenced by the peers. Therefore, a study was carried out to educate the School going adolescent girls living in urban slums of Hyderabad, Telangana, India on right nutrition. Methods –The study was carried out in two randomly selected government schools after obtaining approval from the Scientific Advisory Committee (SAC). About 200 girls each from eighth and ninth standards were recruited as study subjects. The age of the participants ranged from 13-15 years. After obtaining baseline data, intervention was carried out on 8 focal themes related to nutrition, health and family life education, by using well designed educational material. Results: A significant increment in the knowledge levels on all the focal themes was observed among the adolescent girls in the experimental school. After completion of the study, considering the ethical issues, the control group was also given education on 8 focal themes. Conclusions and Implications: It was observed that an integrated approach in communication methods such as combining print media like charts, folders with electronic media, using CD alongside interpersonal communication significantly improved the knowledge levels of these girls on nutrition and family-life education.